Development of a Rheumatoid Arthritis Education Program using the PRECEDE_PROCEED Model - Nadrian, Haidar (Tabriz University of Medical Sciences, 2011)
Background: In order to help rheumatoid arthritis (RA) patients in carrying out and attaining relevant self-care behaviors and adaptation to the physical limitations of this disease and, consequently, promoting their level of health status, an education program based on the PRECEDE component of the PRECEDE–PROCEED model targeting patients with RA was developed. This paper describes the planning of a RA Patient Education Program (RAPEP) designed to promote their quality of life. Methods: The development of the program began with a comprehensive review of the literature. This included a review of the signs and symptoms of RA, accompanying functional disabilities, previous educational programs and the effect of the disease on the patient’s quality of life. Besides, in order to help inform RAPEP program development, and organize the survey according to the factors identified in the PRECEDE model a cross-sectional survey was applied on a non-probability sample of 181 outpatients in Yazd, center of Iran. Results: The quality of life (QOL) problem identified was the considerable low role functioning, health perception and physical functioning due to chronic pain. One of the most significant modifiable behavioral factors impacting pain and functional limitations was self-care behaviors in RA patients. Higher level of knowledge, attitude, self-efficacy, enabling factors and social support is associated with better self-care behavior. Conclusions: The PRECEDE component of the PRECEDE–PROCEED model provided a comprehensive conceptual framework for the development of RAPEP aiming at RA patients in Yazd. Further research to evaluate this educational program is suggested.